Effects of shenkang injection on renal angiogenesis in mice with unilateral ureteral obstruction (Bangladesh Journal of Pharmacology, 2020)
This study aimed to investigate effects of shenkang injection on angiogenesis in mice with renal fibrosis. C57BL/6J mice after unilateral ureteral obstruction were administrated with different doses of shenkang injection for two weeks. Losartan-administrated mice and Sham-operation mice were as positive and negative controls, respectively. Renal function and vasculature changes were observed, and expressions of VEGF and VEGFR2 were detected. Shenkang injection reduced serum levels of urea nitrogen, creatinine and cystatin C. Shenkang injection alleviated the loss of microvessels, decreased the deposition of collagen fibers, and increased expressions of VEGF and VEGFR2 in the obstructed kidney. These findings indicate that shenkang injection alleviates renal dysfunction and fibrotic changes in mice with renal fibrosis by regulating renal angiogenesis.Video Clip of Methodology:Renal Vasculature by Angiography: 6 min 41 sec:  Click to watch